Keragaman Jenis dan Kondisi Habitat Herpetofauna Paska Kebakaran di Taman Nasional Tesso Nilo-Riau - Muhammad Ali Imron; Wiwid Prayoga; Yogi Alro Aliando (Faculty of Forestry Universitas Gadjah Mada, 2021)
Herpetofauna is poikilotherm and sensitive to temperature change in particular fires, understanding response of these taxa after fire could provide early evidence of ecosystem resilience. It seems very few scientific evidences have been reported for the response of herpetofauna communities after fire. We aim to explore the presence of herpetofauna in the ex-burnt areas of Tesso Nilo National Park in Riau Province and find possible environmental conditions which explain their presence. Field work was conducted during December 2015-February 2016 for collecting presence of diurnal herpetofauna species in burnt and un-burnt areas as well as collecting environmental conditions through transects. Numbers of individual sightings during observation were recorded and measurement of environmental conditions included habitat covers, vegetation density using protocol sampling and nested sampling plots. We also calculated vegetation mortality and composition of dead organic matter for each sites. Fires in 2015 have caused a clear difference on the habitat condition for herpetofauna between burnt and un-burnt, whereas the composition of herpetofauna species was higher in un-burnt areas (10 species) than burnt areas (5 species). Frogs were found in burnt area, confirms their ability to survive in disturbed areas.